1996
DOI: 10.1093/oxfordjournals.jbchem.a021306
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Protein Carbonyls with 2,4-Dinitrophenyl Hydrazine and Its Antibodies by Immunoblot in Two-Dimensional Gel Electrophoresis

Abstract: Protein carbonyls are reported to increase in aging and in pathologies such as Alzheimer's disease and ischemic injury. Detailed study of this important issue has, however, been hampered by lack of an appropriate method to identify individual carbonylated proteins. We describe here an immunoblot method to identify individual carbonylated proteins. We describe here an immunoblot method to investigate protein carbonyls reactive to 2,4-dinitrophenyl hydrazine. Rabbit polyclonal antibodies against 2,4-dinitropheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 28 publications
4
108
0
Order By: Relevance
“…Protein carbonylation was detected by western blotting for DNPH-modified proteins separated by 2D-gel electrophoresis. 24,31 This method detected significant increases in protein carbonylation in HL60 cells after 1-h VP16 treatment (Figure 3b). Figure 3c shows that pretreatment with the antioxidant NAC reduced VP16-induced protein carbonylation to control levels (i), demonstrating that, in this case, carbonylation is a result of ROS and it most likely is not the result of glycation.…”
Section: Ros Signalling Is Important For Vp16-induced Cell Death In Hmentioning
confidence: 91%
See 1 more Smart Citation
“…Protein carbonylation was detected by western blotting for DNPH-modified proteins separated by 2D-gel electrophoresis. 24,31 This method detected significant increases in protein carbonylation in HL60 cells after 1-h VP16 treatment (Figure 3b). Figure 3c shows that pretreatment with the antioxidant NAC reduced VP16-induced protein carbonylation to control levels (i), demonstrating that, in this case, carbonylation is a result of ROS and it most likely is not the result of glycation.…”
Section: Ros Signalling Is Important For Vp16-induced Cell Death In Hmentioning
confidence: 91%
“…However, recent advances in 2D-gel electrophoresis and proteomics have led to renewed interest in the field as it becomes possible to identify the proteins that are modified in this way. [23][24][25] A number of interesting papers have shown that during ageing, protein oxidation in response to ROS are not random, but that some proteins are more susceptible than others. 26 In the case of drosophilae flight muscle, only aconitase and adenine nucleotide translocase showed any increase in carbonylation with age, 26 and in mouse plasma ageing-associated protein oxidation was only seen in two proteins, albumin and transferrin.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods are based on the Schiff base chemistry that is possible with the carbonyl group. The most traditional Schiff base method relied on the 2D Western analysis of DNPHderivatized carbonyl proteins (283) and had early applications in the identification of oxidized proteins in AD brain (74). Using shotgun proteomics methods, tryptic peptides are separated with strong cation exchange (SCX) and/or reversephase (RP) LC and detected by MS.…”
Section: Fig 10 Outline Of Redox Proteomics Approachmentioning
confidence: 99%
“…Alternatively, ELISA assays have been developed for the quantitation of DNPH-derivatised carbonyls [85][86][87]. The same chemistry can be used in combination with gel electrophoresis, followed by an immunodetection [88,89]. Alternatively, Yoo and Regnier [90] have developed a biotinylation strategy for the specific labelling of carbonylated proteins after 2-DE.…”
Section: Carbonyl Detection and Quantificationmentioning
confidence: 99%